The Influence of Income, Education, Consumption and Islamic Corporate Governance on Muzakki's Decision - Indah Septiana (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2022)
Muzakki's decision could have an important role in terms of knowing people’s preferences or tendencies in terms of whether to prefer to pay zakat in formal institutions such as BAZNAS, LAZ, Dompet Dhuafa. or prefer to directly give to mustahiq. This study has limitations in terms of focusing only on analyzing the influence of variable income, education, consumption, and Islamic corporate governance. This research focuses on analyzing the influence of income, education, consumption, Islamic good corporate on muzakki decisions in choosing where to pay zakat in Palembang city. The study data uses secondary and primary data, secondary data to determine the number of populations and samples obtained from the Central Statistics Agency (BPS). This research variable is obtained by directly interviewing and using questionnaires as their intrusion in data collection. Analytical tools are used in analyzing using binary logistic regression. finding from this study shows that income is the deciding factor in the decision to choose where to pay zakat. While based on the results of partially variable tests showed that income, and Islamic Corporate Governance had a positive and significant effect on the decision of the place to pay zakat. While consumption has a negative and significant influence on the decision of choosing place to pay zakat. Overall variables independent (income, education, consumption, Islamic corporate governance) is able to explain the dependent variable (decision to pay zakat) of 83%. The remaining 17 percent was explained by variables outside the model or by other variables that were not studied.